X^3-3x^2-22x+24
the first option is the answer
solution: (x + 4)(x - 1)(x -6) = (x^2 - x + 4x -4)(x - 6)
(x^2 + 3x -4)(x - 6) = x^3 -6x^2 + 3x^2 - 18x - 4x + 24 = x^3 - 3x^2 - 22x + 24
Answer:
(f - g)(x) = 2x - 3
Step-by-step explanation:
(f - g)(x) is defined as subtracting the whole g(x) function from the f(x) function.
Hence, we can define it as:
(3x - 1) - (x + 2)
= 3x - x - 1 - 2
= 2x - 3
Therefore, (f - g)(x) = 2x - 3.
Hope this helped!
Answer:
A
Step-by-step explanation:
Answer:
The total he would have to pay back would be $7,320.44
Step-by-step explanation:
(I'm assuming you want the total amount he needs to pay back)
6700 x 0.10 = 670 per year
670 ÷ 365 = 1.835616438356164
1.835616438356164 × 338 = 620.44
620.44 + 6700 = 7,320.44
Answer:
Equation: y = -3x -2
Graph: Attached below ↓↓↓↓↓
Step-by-step explanation:
The equation is y = -3x + b
We need B at this point.
Since we have a point given to us,( -2, 4)we can input the x and y
Solve:
4 = -3(-2) + b
4 = 6 + b
b = -2
So the equation we have is y = -3x -2
Let's graph the line.
We go 2 units below the x-axis, because the y-intercept is -2, and the slope is -3, so we go down 3 units, and to the right 1.
Picture attached:
-Chetan K